Implementation of character education to maintain a clean environment in social studies learning at elementary schools - Agustina, Elsa; Rendrapuri, Rezy Vianthia; Rustini, Tin (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
This research discusses the implementation of character education to protect the environment in social studies learning. The method used in this research is literature study through books or other literature. This research aims to find out how character education is implemented in elementary schools which is linked to social studies learning, namely protecting the environment. The application of character education is an important thing to implement in the learning process. Character is formed from an early age, therefore, through education in elementary school, it is hoped that students will have good character. The interaction of human life will be related to its environment. Therefore, a caring character is needed in protecting the surrounding environment, one of which is the school environment. Integrating character education can be implemented in social studies learning. So that students are able to understand about protecting the environment and can even implement it in their daily lives.